2009
DOI: 10.1111/j.1600-0404.2008.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis relapses: a multivariable analysis of residual disability determinants

Abstract: Incomplete recovery at 1 month is a predictor of long-term persistence of RD. Higher relapse severity is associated with higher risk of RD. Risk of severe relapses is lower in patients treated with immunomodulating drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 15 publications
1
44
2
Order By: Relevance
“…Studies of these groups have shown quantifiable residual neurologic dysfunction in 40-50% of subjects experiencing relapses. [2][3][4] The degree of residual dysfunction from relapses may well be underestimated in these studies as they measured residual with changes in Expanded Disability Status Scale (EDSS), likely not the most sensitive measure of persistent deficit. These results nicely complement the earlier natural history studies that correlate early relapse frequency and residual with rapidity of reaching disability status scale (DSS) 6.…”
mentioning
confidence: 99%
“…Studies of these groups have shown quantifiable residual neurologic dysfunction in 40-50% of subjects experiencing relapses. [2][3][4] The degree of residual dysfunction from relapses may well be underestimated in these studies as they measured residual with changes in Expanded Disability Status Scale (EDSS), likely not the most sensitive measure of persistent deficit. These results nicely complement the earlier natural history studies that correlate early relapse frequency and residual with rapidity of reaching disability status scale (DSS) 6.…”
mentioning
confidence: 99%
“…57 Residual disability is seen in one third to half of all relapses [59][60][61][62] and is more likely if the relapse is severe, multifocal, initially slow to recover, and in people 30 years or older. 60 62 One study indicates that a lack of recovery from a relapse predicts incomplete remission of future relapses.…”
Section: Recovery From Individual Relapsementioning
confidence: 99%
“…Disease progression was defined as an increase of at least 1.5 points on the Expanded Disability Status Scale (EDSS) score [16]. Disabling relapse was defined as a relapse with a residual disability, which was defined as incomplete recovery at 1 month from a relapse [17,18]. As the panel did not conduct any novel experimental research, no ethics approval was necessary.…”
Section: Methodsmentioning
confidence: 99%